Supercritical Fluid Extraction of Black Pepper's Bioactive Compounds: Solubility and Mass Transfer - Then, Siewping; Panau, Freddie; Samyudia, Yudi (Springer, 2013)
Mass transfer of black pepper’s bioactive compound extracted using supercritical CO2 was studied with the parameters such as range of temperature (45°–55°C), pressure (3,000–5,000 psi), CO2 flow rate (5–10 ml/min), and pepper particle size (0.4–1 mm). The solubility-controlled period and diffusion-controlled period of the extraction curve were examined. Static extraction was performed to calculate solubility, and the value obtained varied from 4.8 to 10.3 kg oil/m3 CO2. Transition time analyzed through extraction curve varied from 18 to 43 min and increased with particle size. Mass transfer rates for solubility-controlled period and diffusion-controlled period were analyzed. The average values were 2.7 × 10−3 kg/m3s and 1.04 × 10−4 kg/m3s, respectively. Particle size was found to be the dominant factor during solubility-controlled period, while pressure was the key factor for the intra-particle diffusion. The fluid-phase mass transfer coefficients and diffusivity were calculated based on Sovova’s model.